CHOLANGIOCARCINOMA: EPIDEMIOLOGY, HISTOPATHOLOGY, AND POTENTIAL PROGNOSTIC AND THERAPEUTIC IMPLICATIONS IN A COHORT FROM A REFERENCE CENTER IN SOUTHERN BRAZIL - João Pedro Pattussi BERTINATTI; Josenel Maria Barcelos MARÇAL; Eduardo CAMBRUZZI; Dido Eliphas LEÃO DE ALENCAR (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Cholangiocarcinoma (CCA) is a rare neoplasm, with high mortality, originating in the bile ducts. Its incidence is higher in Eastern countries due to the endemic prevalence of liver parasites. Factors such as metabolic syndrome, smoking, and pro-inflammatory conditions are also linked to the disease. Clinical features include asthenia, abdominal pain, cholestasis, and increased serum levels of CEA and CA19-9. AIMS: The aim of this study was to evaluate CCA prevalence, survival, and potential prognostic and therapeutic implications in a patient cohort and assess correlations with clinical laboratory data and possible associated risk factors. METHODS: This is a retrospective study of the clinical and histological data of patients diagnosed with CCA at Santa Casa de Misericórdia in Porto Alegre, Brazil, between 2016 and 2021. RESULTS: There was a 56% prevalence of CCA in women, with intrahepatic localization in 55.4% of cases and unifocality in 85.6% of patients. The mean age of the patients was 63 years (26–89 years), with a mean tumor size of 5.5 cm. The median survival time was 7 months (0 to >50). CA19-9 was altered in 81% of patients, whereas GOT/GPT was altered in 62.5% and gamma-glutamyl transferase/alkaline phosphatase/bilirubin in 69.1% of patients. Mortality was higher among patients with extrahepatic CCA. CONCLUSION: Risk factors such as smoking, cholecystectomy, cirrhosis, intrahepatic lithiasis, and transplantation should be considered individually by the attending physician for radiological monitoring and incidental discovery of the neoplasm. Lack of timely identification by the attending physician can delay diagnosis, increasing mortality.